Can Aquatic Plants Keep Pace with Climate Change? - Viana, Duarte S. (Frontiers in Plant Science, 2017)
The persistence of species may depend upon their capacity to keep pace with climate change. However, dispersal has been ignored in the vast majority of studies that aimed at estimating and predicting range shifts as a response to climate change. Long distance dispersal (LDD) in particular might promote rapid range shifts and allow species to track suitable habitat. Many aquatic plant species are dispersed by birds and have the potential to be dispersed over hundreds of kilometers during the bird migration seasons. I argue that such dispersal potential might be critical to allow species to track climate change happening at unprecedented high rates. As a case study, I used dispersal data from three aquatic plant species dispersed by migratory birds to model range shifts in response to climate change projections. By comparing four dispersal scenarios – (1) no dispersal, (2) unlimited dispersal, (3) LDD <100 km and (4) LDD mediated by bird migratory movements –, it was shown that, for bird-mediated dispersal, the rate of colonization is sufficient to counterbalance the rate of habitat loss. The estimated rates of colonization (3.2 - 31.5 km·year-1) are higher than, for example, the rate of global warming (previously estimated at 0.42 km·year-1). Although further studies are needed, the results suggest that these aquatic plant species can adjust their ranges under a severe climate change scenario. Therefore, investigating the dispersal capacity of species, namely their LDD potential, may contribute to estimate the likelihood of species to keep pace with climate change.